TOC - and Emerging Technology., International Journal of Engineering (International Journal of Engineering and Emerging Technology; Vol 5 No 2 (2020): July - DecemberDO - 10.24843/IJEET.2020.v05.i02.p00, 2020)
Cover Vol 5 No 2